Pembiasaan Karakter Peserta Didik di Mi Ma’arif Wotbuwono - Pramono, Ibnu Jati; Sabitussolikhah, Nurul; Amrissadiah, Nurul Aulia; Fauziah, Muna (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2025)
This study aims to describe the character habituation practices implemented at MI Wotbuwono through a series of daily and weekly religious activities. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings reveal that character habituation is carried out through morning greetings and handshakes, Qur’anic reading and memorization activities (RTQ) based on students’ levels, recitation of Asmaul Husna before lessons, scheduled dhuha prayer and tahlil, and daily congregational Dzuhur prayer. All activities are supervised by teachers and implemented consistently, contributing to the formation of students’ religious character, discipline, responsibility, and noble behavior. The results indicate that systematic habituation serves as an effective strategy for character education in Islamic elementary schools.